Attitudes toward molecular testing for personalized cancer therapy. Issue 2 (10th September 2014) - Yusuf, Rafeek A.; Rogith, Deevakar; Hovick, Shelly R. A.; Peterson, Susan K.; Burton‐Chase, Allison M.; Fellman, Bryan M.; Li, Yisheng; McKinney, Carolyn; Bernstam, Elmer V.; Meric‐Bernstam, Funda
Abstract : BACKGROUND: This study assessed attitudes of breast cancer patients toward molecular testing for personalized therapy and research. METHODS: A questionnaire was given to female breast cancer patients presenting to a cancer center. Associations between demographic and clinical variables and attitudes toward molecular testing were evaluated. RESULTS: Three hundred eight patients were approached, and 100 completed the questionnaire (a 32% response rate). Most participants were willing to undergo molecular testing to assist in the selection of approved drugs (81%) and experimental therapy (59%) if testing was covered by insurance. Most participants were white (71%). Even if testing was financially covered, nonwhite participants were less willing to undergo molecular testing for the selection of approved drugs (54% of nonwhites vs 90% of whites, odds ratio [OR] = 0.13, P = .0004) or experimental drugs (35% vs 68%, OR = 0.26, P = .0072). Most participants (75%) were willing to undergo a biopsy to guide therapy, and 46% were willing to undergo research biopsies. Nonwhite participants were less willing to undergo research biopsies (17% vs 55%, OR = 0.17, P = .0033). Most participants wanted to be informed when research results had implications for treatment (91%), new cancer risk (90%), and other preventable/treatable diseases (87%). CONCLUSIONS: Most patients were willing to undergo molecular testing and minimally invasive procedures to guide approved or experimental therapy. There were significant differences in attitudes toward molecular testing between racial groups; nonwhites were less willing to undergo testing even if the results would guide their own therapy. Novel approaches are needed to prevent disparities in the delivery of genomically informed care and to increase minority participation in biomarker‐driven trials. Cancer 2015;121:243–50 . © 2014 American Cancer Society . Abstract : The authors assess the attitudes of 100 breast cancer patients regarding molecular testing for personalized therapy and research with a questionnaire. Most patients are willing to undergo molecular testing and minimally invasive procedures to guide approved or experimental therapy, but there are significant differences in attitudes toward molecular testing between racial groups.